URGENSI ARAH KIBLAT DALAM PELAKSANAAN AKAD NIKAH DI KECAMATAN TIROANG KABUPATEN PINRANG PERSPEKTIF ILMU FALAK - Nur Azzah; Wakia, Nurul (Universitas Islam Negeri Alauddin Makassar, 2025)
The marriage contract is a sacred moment in the life of Muslims that is full of spiritual and symbolic values. In some Muslim areas, including in Tiroang Sub-district, Pinrang District, the conduct of marriage contracts is influenced not only by Islamic law but also by local traditions and culture. One important element that has come under scrutiny is the orientation of the Qibla direction in the ijab kabul procession. This study aims to reveal the perceptions of the community and local religious leaders on the urgency of Qibla direction in the marriage contract and analyze it from the perspective of Islamic astronomy. The method used is qualitative-descriptive with a shar'i and sociological approach, through observation, semi-structured interviews and documentation. The results show that although the Qibla direction is not a valid condition of the marriage contract in fiqh, most people have begun to interpret the Qibla direction as a form of ta'dzim (reverence) and a spiritual symbol. The Islamic astronomy, with its hisab and rukyat methods, contributes significantly to the precise determination of Qibla direction, while strengthening religious values in socio-religious practices. This study indicates that there is a harmonious blend of local culture, religious values and contemporary Islamic science. The Qibla direction in the marriage contract is not only understood as a physical position, but also as a symbol of servitude and seriousness in carrying out worship to Allah swt..